'Clear educational routes': An example of conservative modernization in Swedish upper secondary schools. (24th October 2015) - Loeb, Ingrid Henning; Wass, Karin Lumsden
This article concerns the development of education for young students in Sweden who do not attend regular pathways in upper secondary education, and analyses the changes of educational policy and the organizing of teaching for this group of students. The centre of interest is the upper secondary educational reform carried out in 2011. With this reform, a structure of five 'clear educational routes' was established for students who did not fulfil the eligibility requirements for the regular programmes. We show how, since the reform of 2011, two diverse national policies have co-existed regarding the organizing of studies for students outside the regular programmes: on the one hand a policy with imperatives of clarity, and on the other hand indistinct guidelines and with delegation. A survey of municipalities in two districts on the local organizing of the introductory programmes provides results. In this new era of 'clear educational routes' an increasingly differentiated, ambiguous and fragmented upper secondary school system is taking shape.